Our Constitution - Ritchie, Donald A., frey50; JusticeLearning.org. (Oxford ; New York : Oxford University Press, 2006)
An in-depth look at the entire text of the U. S. Constitution, annotated with detailed explanations of its terms and contents. Each Amendment and Article is accompanied by sidebar material on the history of its application, including profiles of important Supreme Court cases, texts of related primary source documents, and contemporary news articles. Double-page timelines for several of the Articles and all the Amendments highlight important events and legal cases. Includes facsimile reproductions of primary source documents, paintings, phots, and historical artifacts.--From publisher description.
Why was the Constitution necessary? -- What kind of government did the Constitution create? -- What rights does the Constitution protect? -- How has the Constitution expanded over time? -- How is the Constitution interpreted?
Keywords: Constitutional law -- United States; Constitutions -- United States